THE INFLUENCE OF FINANCIAL LITERACY, FINANCIAL BEHAVIOR, FINANCIAL TECHNOLOGY, AND OVERCONFIDENCE ON INVESTMENT DECISIONS AMONG GENERATION Z - Dinda Rizkina; Desi Handayani; Firman Surya (SOSIOEDUKASI, 2025)
Effective individual investment decision-making relates to one's level of financial literacy and behavior. Generation Z, which is characterized by digital adaptability, shows varying levels of financial understanding and confidence in managing investments. Meanwhile, the development of financial technology provides easier digital access to various investment platforms. This study aims to determine the effect of financial literacy, financial behavior, financial technology, and overconfidence on investment decisions among Generation Z in Padang City. This study uses a quantitative approach. Data were collected through the distribution of questionnaires to respondents. The population in this study consists of Generation Z individuals in Padang City, with a total sample of 545 respondents obtained using random sampling techniques. The results of this study show that financial literacy has a significant effect on investment decisions. Financial behavior also significantly influences investment decisions. Financial technology is also proven to have a significant effect. Likewise, overconfidence has a significant influence on investment decisions. The study also indicates that financial literacy, financial behavior, financial technology, and overconfidence simultaneously have a significant influence on investment decisions.